A new experimental approach to lithium-ion battery fires in electric vehicles: Investigation of fire behavior and effectiveness of extinguishing agents - Onur Mammacıoğlu; Gokhan Coskun (Case Studies in Thermal Engineering, 2025)
This study investigates fire incidents in lithium-ion batteries used in electric vehicles and evaluates the effectiveness of extinguishing agents under controlled conditions, highlighting the difficulty of extinguishing such fires due to the materials in the lithium-based battery components. The combustion of 18,650 Lithium Nickel Manganese Cobalt Oxide (NMC) batteries was initiated using an overheating method in a specialized safety setup. The extinguishing agents tested include Water, BIOVERSAL, NOVEC 1230, and COG (high-viscosity liquid substance). The first phase involved a single-battery combustion test, followed by intervention tests under two conditions, which were the heat supply cut off and continuous heat application. Performance was evaluated based on combustion and explosion temperatures, ignition delay, and variations in ambient gas composition (O2, CO, CO2). Under heat-cut conditions, BIOVERSAL exhibited superior thermal resistance (∼247,6 °C), while Water provided a longer ignition delay of about 82 s. In continuous heat conditions, COG achieved the highest explosion temperature (∼247 °C) and longest ignition delay about 75 s, significantly outperforming NOVEC 1230, which showed the lowest suppression efficiency. In conclusion, BIOVERSAL and COG were the most effective extinguishing agents, with BIOVERSAL excelling under heat-cut conditions and COG proving most efficient under continuous heat exposure.